Atypical Presentation of Cytomegalovirus-Related Infantile Nephrotic Syndrome - Fallahzadeh, Mohammad Amin; Fallahzadeh, Fatemeh; Vahhab, Elham; Fallahzadeh, Mohammad Hossein (Journal of Pediatric Nephrology, 2019)
Nephrotic syndrome is the most common glomerular disease in children. Most cases are idiopathic and the first episode is rarely related to cytomegalovirus infection, particularly after 3 months of age. We present a 7-month-old infant who developed atypical presentation of nephrotic syndrome secondary to cytomegalovirus infection. The patient was referred to undergo orchipexy due to right-sided undescended testis. Following the surgery, he developed fever, gastroenteritis and renal failure. A few days later, generalized edema and proteinuria were detected. Due to positive test results for cytomegalovirus, ganciclovir was administered. Remission of nephrotic syndrome was obtained within the first two weeks of the treatment. No relapse of nephrotic syndrome was detected during 12 months of follow up. We may conclude that in unexplained infantile nephrotic syndrome, CMV should be considered as one of the possible etiologies. Keywords: Nephrotic Syndrome; Cytomegalovirus; Infant; Ganciclovir; Edema; Proteinuria; Gastroenteritis.